Pengaruh Internet Financial Reporting dan Tingkat Pengungkapan Informasi Website Terhadap Frekuensi Perdagangan Saham - Sri Fitri Wahyuni; Radiman Radiman; Yogi Pranata (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The purpose of this study was to analyze the effect of Internet Financial Reporting (IFR) practices on the frequency of stock trading of companies listed on the Stock Exchange in order to analyze the effect of corporate website-based information disclosure rates on stock trading frequency and analyze the effect of IFR practice and Website-Based Level of Disclosure of Information on Stock Trading Frequencies Companies listed on the IDX. The sampling technique in this study was carried out using a non-probability sampling approach, specifically the purposive sampling method, which is a sampling technique with a non-random sampling method but based on specific objectives and considerations or criteria. The results of this study prove that the effect of IFR practices has a significant effect on the frequency of trading of shares of companies listed on the IDX. Effect of Website Information Disclosure Level significantly influence the Frequency of Stock Trading of companies listed on the IDX. The effect of IFR practices and the level of website information have a significant effect on the Frequency of Stock Trading of companies listed on the Indonesia Stock Exchange